1993
DOI: 10.4319/lo.1993.38.8.1633
|View full text |Cite
|
Sign up to set email alerts
|

Exopolymer microenvironments of microbial flora: Multiple and interactive effects on trophic relationships

Abstract: Microbial cells in natural environments arc often encased in different types of exopolymcr secretions (EPS), ranging from tight capsules surrounding individual cells to the looser slime matrices of biofilms. The diffcrcnt physical and chemical propertics of exopolymers could have secondary effects on trophic interactions between microbial cells and consumer animals. Laboratory studies showed that capsule EPS is significantly less digestible to consumers than slime EPS, even when extracted from the same bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
94
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(97 citation statements)
references
References 18 publications
(25 reference statements)
2
94
0
1
Order By: Relevance
“…Carlton and Wetzel (1988) showed that epipelic algal photosynthesis, or the magnitude of sediment oxygenation, was inversely correlated with the phosphate efflux rate from lake sediments. The associated production of carbohydrates in response to the nutrient-depleted conditions may slow down the diffusion of ions and contribute to the conservation of nutrients in sediment (Decho 1994). Primary production in the overlying water may be affected by the formation of bubble mats if nutrients become conserved within the sediment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Carlton and Wetzel (1988) showed that epipelic algal photosynthesis, or the magnitude of sediment oxygenation, was inversely correlated with the phosphate efflux rate from lake sediments. The associated production of carbohydrates in response to the nutrient-depleted conditions may slow down the diffusion of ions and contribute to the conservation of nutrients in sediment (Decho 1994). Primary production in the overlying water may be affected by the formation of bubble mats if nutrients become conserved within the sediment.…”
mentioning
confidence: 99%
“…An dxopolymer matrix is a highly labile source of carbon and e$hibits highly adsorptive qualities that allow it to sequester dissolved organic matter (Decho and Lopez 1993). The flux of this material to the overlying water column can serve as a measure of food availability, an important parameter not often considered in the development of carrying capacity models for shellfish aquaculture in coastal embayments (Dowd 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Одной из главных функций ЭПС в морских экосистемах является биостабилизация осадков, необходимая для сохранения структуры подверженных эрозии литоральных зон (Paterson, 1989;Decho, 1990;Decho et al, 1993). Они заполняют межклеточное пространство микробных агрегатов и формируют структуру матрикса биопленок.…”
Section: Introductionunclassified
“…Cyanobacteria are pioneer species with good adaptive skills, able to colonize barren sediments and soils, fix nitrogen and carbon, and regulate moisture-producing exopolymeric secretions: bacterial capsules, sheaths, and slime of hydrophilic polysaccharides (Decho and Lopez 1993) with variable water content that change with environmental conditions and strain type. These polysaccharides act as protection from sudden osmotic changes and desiccation (Klock et al 2007), allowing cell adhesion to substrata.…”
Section: Introductionmentioning
confidence: 99%